ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN PADA KANTOR CAMAT MEDAN TEMBUNG - Eliza Handayani Lubis; Karin Sarah Angelina Siahaan; Putri Kemala Dewi Lubis; Sarah Bakara (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
In accountability and transparency, the quality of financial reports is assessed through the preparation of the report. This is done to provide accountability and transparency in financial reporting. Accountability itself is an ethical concept that is closely related to government management, which includes the government executive, parliamentary legislature and judiciary, and has different definitions (Herindraningrum & Yuhertiana, 2021). Therefore, accountability is needed in the management of public funds and transparency is needed to ensure that financial management can be trusted. The relationship between the regional head as a member of the community and the regional head as an agent chosen by the community. Regional governments are responsible for the authority given to the community (Larasati Agustina & Bagito, 2019). The regional people's representative council plays a role in developing the supervisory function of regional government. To improve the quality of local government, community needs can be used as a reference so that local government can operate well and produce trustworthy and open financial reports (Indrayani & Widiastuti, 2020).